2003
DOI: 10.7863/jum.2003.22.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Complications After Interventional Sonography of Focal Liver Lesions

Abstract: Sonographically guided diagnostic biopsy of focal liver lesions and liver abscess drainage are safe procedures. In contrast, liver tumor ablation procedures have a low but definite risk of mortality and major complications. Puncture of hydatid cysts must be performed only in institutions that can treat anaphylactic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 40 publications
3
30
0
4
Order By: Relevance
“…Rates of seeding after biopsy range greatly. While modest rates of tumor dissemination of 0.003%-0.009% have been described [23][24][25] , a review on the subject has described incidences of 5% [26] . A recent systematic review and a meta-analysis [27] on needle track seeding following biopsy of liver lesions indicative of HCC showed that the incidence is 2.7% overall [95% Confidence Interval (CI), 1.8-4], and 0.9% per year (95% CI, 0.6-1.3).…”
Section: Needle Tract Seedingmentioning
confidence: 99%
“…Rates of seeding after biopsy range greatly. While modest rates of tumor dissemination of 0.003%-0.009% have been described [23][24][25] , a review on the subject has described incidences of 5% [26] . A recent systematic review and a meta-analysis [27] on needle track seeding following biopsy of liver lesions indicative of HCC showed that the incidence is 2.7% overall [95% Confidence Interval (CI), 1.8-4], and 0.9% per year (95% CI, 0.6-1.3).…”
Section: Needle Tract Seedingmentioning
confidence: 99%
“…In another large series, 16,648 guided biopsies and 3035 therapeutic procedures were analyzed in 13,222 patients. Overall mortality was 0.06% (none after diagnostic procedures) [8]. In a series of 159 HCC patients undergoing fine needle aspiration, four (2.5%) bled significantly, one of whom died [9].…”
mentioning
confidence: 99%
“…Unlike other locally ablative therapies such as radiofrequency ablation, chemoembolization, ethanol injection ablation, and cryoablation, which cause tissue necrosis and its associated side effects [1][2][3] such as infection, fever, scarring, inflammation, and pain, the Litx TM system is a non-thermal therapy with minimal side effects [8]. Other locally ablative therapies present significant limitations with respect to lesion size and location of lesion relative to critical structures, and exhibit little or no prospect for repeat treatment [19] Evaluations by RECIST criteria.…”
Section: Tumor Response and Time To Progressionmentioning
confidence: 99%
“…While showing promise for the treatment of otherwise intractable liver malignancies, interstitial ablative techniques such as cryoablation and thermal ablation using radiofrequency and ultrasound all produce significant side effects [1][2][3]. One commonality among these approaches is the induction of tissue necrosis, resulting in cytokine cascade activation and upregulation of growth factors such as tumor necrosis factor a, leading to mononuclear cell infiltration and often potentiating a sepsis-like condition [4].…”
Section: Introductionmentioning
confidence: 99%